An investigation of full body kinematics for static and dynamic throw-in in proficient and non-proficient soccer players when they tried to hit a specific target - Barraza, L. C. H.; Yeow, C. H. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
The purpose of this study was to identify the kinetic differences between proficient and non-proficient players during one ability: Throw-in. Twelve players were recruited from the local university to perform the experiment. Many studies have been conducted to explain the biomechanics of this ability, however there is about a lack of research, investigating the comparison between proficient and non-proficient players. The hypotheses of this study were that a) peak knee flexion angles would be higher for dynamic style for proficient and less proficient subjects, and b) peak vertical ground reaction force (GRF) would be higher for the dynamic style. Our results showed a markedly difference in the peak flexion angles for proficient players. The results may be useful to develop training strategies to help to the players to achieve precise throws.